https://doi.org/10.36873/ KARAKTERISTIK SPEKTRA FTIR DAN SIFAT HIDROFOBISITAS TANAH GAMBUT PEDALAMAN PADA PENGGUNAAN LAHAN YANG BERBEDA DI KABUPATEN PULANG PISAU: FTIR Spectrum and Hydrophobicity Characteristic of Inland Peat soil with different land use from Pulang Pisau - Zafrullah Damanik; Fengky Florante Adjie; Nina Yulianti; Melhanah Melhanah; Sustiyah Sustiyah; Y Sulistiyanto; T Sigalingging (AgriPeat, 2021)
The irreversible drying indicated by the hydrophobic characteristic is one of the characteristics of peat which can be used to indicate the level of peatland degradation. Hydrophobic peat usually occurs as a result of fire or intensive drought which is mainly caused by peat land conversion. The objective of this research is to study the effect of land use on peat hydrophobicity, based on FTIR spectra and water penetration drop time. The result show that hydrophobicity characteristics of peat is influence by land use differences. The abandoned or scrub land has higher hydrophobic characteristic which indicated by slow water penetration time and the higher hydrophobic index based on the FTIR method, compared with rubber and palm oil plantation. Organic compounds that appear and cause peat to become hydrophobic include carboxyl, hydroxyl phenolic groups, and high lignin content.